THE USE OF THE METHODS OF EXTRACORPORAL HEMOCORRECTION IN COMPLEX TREATMENT OF MALIGNANT TUMORS AND REHABILITATION OF CANCER PATIENT - I. R. Gilmutdinova; P. S. Eremin; A. D. Fesyun; A. V. Butenko (Сибирский онкологический журнал)
The purpose of the study was to analyze literature data on the use of extracorporal hemocorrection as a pathogenetically significant component of rehabilitation for cancer patients.Material and Methods. Literature search was carried out using keywords: rehabilitation of cancer patients, plasmapheresis, extracorporeal hemocorrection, hemodialysis. Out of 250 selected articles, 42 were used to write a review.Results. Methods of extracorporeal hemocorrection are successfully used in the treatment of a wide range of diseases; therefore, the feasibility of applying these methods for rehabilitation of cancer patients is being studied. The review presents literature data on the feasibility of using the methods of extracorporal hemocorrection methods to compensate for the pathophysiological processes related to cancer development.Conclusion. The analysis shows that a positive experience of using the methods of extracorporal hemocorrection for rehabilitation of cancer patients has been gained. However, no clear criteria for the application of these methods and for the assessment of their effectiveness have been developed.